Meningkatkan Kepercayaan diri dalam Public Speaking untuk Berdakwah - Auliya Zachani, Nur Salsa; Tia Nur Amrina; Suryandari, Meity (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Public Speaking is the process of speaking in public or an audience to convey information and influence the audience. Public speaking is also a skill. practice, and the process of giving a speech or speaking in front of a wide audience. The aim is to: Convey information, influence, express opinions, motivate, entertain. Self-confidence is a trait that a person has and is confident in his abilities. Self-confidence is very useful when we are speaking in front of many people. The relationship between public speaking and da'wah communication requires a change in the views or behavior of the audience to fulfill the wishes of the message conveyed. Thus, what has been conveyed by the preacher or communicator can influence the behavior of the communicant or mad'u to the extent of the communicator's ability to influence the development of the da'wah.